Crossover from dirty to clean superconducting limit in dc magnetron-sputtered thin Nb films - Dobrovolskiy, O.V.; Huth, M. (Elsevier, 2012)
High-quality Nb (110) thin films with residual resistance ratios up to 60 and critical temperatures Tc≈9.27 K have been prepared by conventional dc-magnetron sputtering on α-Al2O3 by careful selection of the sputtering conditions. This allowed for a systematic study of the influence of the growth rate on the structural quality and the superconducting properties of the films. The optimized growth conditions were revealed at the substrate temperature Ts=850 °C, Ar pressure Ps=0.4 Pa, and the growth rate g≃0.5 nm/s. The results of the films' structural characterization by X-ray diffraction, reflection high-energy electron diffraction, and atomic force microscopy are presented. In terms of the electron mean free path l and the superconducting coherence length ξ, deduced from the magneto-resistivity data, the clean superconducting limit (l>ξ) is realized in the high-purity films. For comparison, in impure Nb films sputtered at room temperature while keeping the rest of the sputtering parameters unvaried, the opposite dirty limit (ξ≳l) ensues. The merits of these findings are discussed in the context of the demands of present-day fluxonics devices regarding the normal-state and flux-flow properties of superconducting films they are made of.
Keywords: Epitaxial Nb films DC magnetron sputtering Clean and dirty superconducting limits Critical temperature Residual resistivity